Review of Islamic Law concerning underage child labor (Comparative study with Labor Law No. 13 of 2003) - Lutfhfiah, Rifkah Nurul; Mahfud, Imam; Turmidzi, Imam (Priviet Social Sciences Journal, 2022)
The practice of child labor is currently rife everywhere, not infrequently there are still many companies that employ minors because of budget efficiency, due to low wages, in practice sometimes companies do not provide rights that should be given to child workers. On the other hand, children are the responsibility of parents who should be given their rights and parents must fulfill the responsibility for the gift of children that God has given to provide a living and a good education. This research includes field research, the results of which will be presented descriptively with qualitative analysis. The results of this study indicate that Islam says that children are prohibited from doing work if the work is not based on their own will and is coercion from parents to earn a living, but it is permissible if the work is done according to the child's will and is a type of light work that can be done by children.